TRPV1 and TRPM8 in Treatment of Chronic Cough - Eva Millqvist (Pharmaceuticals, 2016)
Chronic cough is common in the population, and among some there is no evident medical explanation for the symptoms. Such a refractory or idiopathic cough is now often regarded as a neuropathic disease due to dysfunctional airway ion channels, though the knowledge in this field is still limited. Persistent coughing and a cough reflex easily triggered by irritating stimuli, often in combination with perceived dyspnea, are characteristics of this disease. The patients have impaired quality of life and often reduced work capacity, followed by social and economic consequences. Despite the large number of individuals suffering from such a persisting cough, there is an unmet clinical need for effective cough medicines. The cough treatment available today often has little or no effect. Adverse effects mostly follow centrally acting cough drugs comprised of morphine and codeine, which demands the physician’s awareness. The possibilities of modulating airway transient receptor potential (TRP) ion channels may indicate new ways to treat the persistent cough “without a reason”. The TRP ion channel vanilloid 1 (TRPV1) and the TRP melastin 8 (TRPM8) appear as two candidates in the search for cough therapy, both as single targets and in reciprocal interaction.